A case of non-O1/non-O139 Vibrio cholerae septicemia and meningitis in a neonate. (June 2015) - Hao, Yingying; Wang, Yueling; Bi, Zhenwang; Sun, Baixiu; Jin, Yan; Bai, Yuanyuan; Chen, Baoli; Shao, Chunhong; Sun, Xuerong; Lu, Zhiming
Highlights: We report a rare case of septicemia with meningitis due to non-O1/non-O139 Vibrio cholerae in a neonate. We examined the genotype and phenotype of the isolate in relation to pathogenicity. Multilocus sequence typing (MLST) was performed to establish the genetic heterogeneity of the isolate. Non-O1/non-O139 Vibrio cholerae should be added to the differential diagnosis of neonatal septicemia and meningitis. Summary: A case of septicemia with meningitis due to non-O1/non-O139 Vibrio cholerae in a neonate is reported. The genotype and phenotype of the isolate were examined in relation to the major virulence genes. The isolate was shown to be non-toxin but cytotoxin-producing, distinguished from the dominant clone of non-O1/non-O139  V. cholerae by multilocus sequence typing.